Implementasi Model Pembelajaran PAI Berbasis Multikultural dalam Membina Siswa Bertoleransi Agama pada Siswa di SMP Negeri 3 Genteng - Rifqi, Ahmad Sihabudin; Syahid, Mar; Fitria, Mulajimatul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) STIB Banyuwangi, 2024)
The purpose of this study is to describe the form of a multicultural-based Islamic Religious Education learning model in fostering students to tolerate students' religions and the obstacles to implementing a multicultural-based Islamic Religious Education learning model in promoting students to tolerate religions at SMP Negeri 3 Genteng. This type of research is qualitative research. The researcher's data collection technique uses interviews, documentation, and documentation. Data analysis used in this study is interactive analysis, namely; data collection, data reduction, data presentation, and conclusion. The results of this study indicate that the multicultural-based Islamic Religious Education (PAI) learning model at SMP Negeri 3 Genteng has great potential to foster an attitude of tolerance among students from various religious and cultural backgrounds. Despite facing obstacles such as student prejudice, lack of teacher understanding of multiculturalism, limited resources, and time in the curriculum, collaboration between teachers, students, parents, and the community can overcome these challenges. With the right steps, it is hoped that students can become tolerant individuals ready to contribute to a diverse society